PERHITUNGAN KAPASITAS TRAFO PEMBUMIAN TITIK NETRAL PADA GENERATOR - Juara Mangapul Tambunan; Tony Koerniawan; Ganjar Ramadhan (Sekolah Tinggi Teknik - PLN, 2015)
Generator is an important component of plant. Therefore the reliability and sustainability of a generator in generating electricity depends on the grounding system used. The transformer capacity generated from the calculation of 33.045 kVA in the event of interference. So the capacity of the transformer used must exceed the capacity of the transformer during interruption.